IMPLEMENTATION OF WORD OF MOUTH MARKETING COMMUNICATION STRATEGIES IN MICRO SMALL MEDIUM BINGGO SCREEN PRINTING PAJARAKAN PROBOLINGGO - Bashori Alwi (Assets Journal: Journal of Economic and Business, 2023)
The purpose of this study is to find out the procedure for implementing word of mouth marketing communication strategies in the Binggo Screen Printing Pajarakan Probolinggo business and the impact of implementing word of mouth marketing communications on business income for Binggo Screen Printing Pajarakan Probolinggo. To answer these problems, field research and descriptive qualitative approaches were used, with data collection techniques through interviews, observation, documentation and triangulation. From the results of the study it can be concluded that the application of word of mouth marketing communication strategies to micro, small and medium enterprises Binggo Screen Printing Pajarakan Probolinggo is quite good, by implementing two types of word of mouth strategies namely organic word of mouth and amplified word of mouth. The results of implementing the word of mouth communication strategy also have a good impact on revenue from Binggo Screen Printing due to the increasing number of new consumers after the implementation of word of mouth as a marketing communication strategy.